CXC-chemokine regulation and neutrophil trafficking in hepatic ischemia-reperfusion injury in P-selectin/ICAM-1 deficient mice - Crockett Elahé T; Dowlatshahi Shadi; Monson Keith M (BMC, 2007)
Abstract Background Neutrophil adhesion and migration are critical in hepatic ischemia and reperfusion injury (I/R). P-selectin and the intercellular adhesion molecule (ICAM)-1 can mediate neutrophil-endothelial cell interactions, neutrophil migration, and the interactions of neutrophils with hepatocytes in the liver. Despite very strong preclinical data, recent clinical trials failed to show a protective effect of anti-adhesion therapy in reperfusion injury, indicating that the length of injury might be a critical factor in neutrophil infiltration. Therefore, the aim of this study was to assess the role of P-selectin and ICAM-1 in neutrophil infiltration and liver injury during early and late phases of liver I/R. Methods Adult male wild-type and P-selectin/ICAM-1-deficient (P/I null) mice underwent 90 minutes of partial liver ischemia followed by various periods of reperfusion (6, 15 h, and a survival study). Liver injury was assessed by plasma level of alanine aminotransferase (ALT) and histopathology. The plasma cytokines, TNF-α, IL-6, MIP-2 and KC, were measured by ELISA. Results Reperfusion caused significant hepatocellular injury in both wild-type and P/I null mice as was determined by plasma ALT levels and liver histopathology. The injury was associated with a marked neutrophil infiltration into the ischemic livers of both wild-type and P/I null mice. Although the levels of ALT and neutrophil infiltration were slightly lower in the P/I null mice compared with the wild-type mice the differences were not statistically significant. The plasma cytokine data of TNF-α and IL-6 followed a similar pattern to ALT data, and no significant difference was found between the wild-type and P/I null groups. In contrast, a significant difference in KC and MIP-2 chemokine levels was observed between the wild-type and P/I null mice. Additionally, the survival study showed a trend towards increased survival in the P/I null group. Conclusion While ICAM-1 and P-selectin does not appear to be critical for neutrophil infiltration and I/R injury in the liver, they may regulate CXC-chemokine production. Blockage of these adhesion molecules may improve survival and remote organ injury that often accompanies liver I/R injury, through chemokine regulation.